Job satisfaction among public health professionals working in public sector: a cross sectional study from Pakistan - Kumar, Ramesh (BioMed Central, 2013)
BACKGROUND: Job satisfaction largely determines the productivity and efficiency of human resource for health. It literally depicts the extent to which professionals like or dislike their jobs. Job satisfaction is said to be linked with the employee’s work environment, job responsibilities and powers and time pressure; the determinants which affect employee’s organizational commitment and consequently the quality of services. The objective of the study was to determine the level of and factors influencing job satisfaction among public health professionals in the public sector. METHODS: This was a cross sectional study conducted in Islamabad, Pakistan. Sample size was universal including 73 public health professionals, with postgraduate qualifications and working in government departments of Islamabad. A validated structured questionnaire was used to collect data from April to October 2011. RESULTS: Overall satisfaction rate was 41% only, while 45% were somewhat satisfied and 14% of professionals highly dissatisfied with their jobs. For those who were not satisfied, working environment, job description and time pressure were the major causes. Other factors influencing the level of satisfaction were low salaries, lack of training opportunities, improper supervision and inadequate financial rewards. CONCLUSION: Our study documented a relatively low level of overall satisfaction among workers in public sector health care organizations. Considering the factors responsible for this state of affairs, urgent and concrete strategies must be developed to address the concerns of public health professionals as they represent a highly sensitive domain of health system of Pakistan. Improving the overall work environment, review of job descriptions and better remuneration might bring about a positive change.